Advancing evidence-based treatment of infectious diseases in children with real-world data: Opportunities and challenges - Radtke, Kendra K.; Butte, Atul J. (Frontiers in Pharmacology, 2023)
There is an increased interest in utilizing real-world data (RWD) for pharmaceutical research and regulatory decision-making. The development and use of pediatric medicines could benefit greatly from RWD studies given nearly half of drugs prescribed to children are “off-label”, meaning there is a lack of pediatric-specific evidence from controlled trials, while there is an abundance of data from routine clinical practice. Currently, the use of RWD, such as data from electronic health records, is lacking in pediatric research, especially within infectious diseases. Here, we discuss opportunities and challenges for RWD to generate evidence on the optimal treatment and management of infectious diseases in children.